Paradoxes in the System: Public Service Sport Broadcasting between Mandate and Market - Christoph Bertling (Athens Journal of Sports, 2026)
The allocation of sports broadcasting rights has become a central field of media law, competition law, and democratic theory in Europe. This article argues that public service broadcasters occupy a structurally paradoxical position within the sports rights market: they simultaneously function as competitive market actors and as constitutionally mandated providers of public value. This dual role generates persistent tensions between market rationality and democratic communication requirements. The article develops a legal-economic analysis of this paradox, focusing on welfare-economic justification, distortions in rights markets, and the fragmentation of public communication through global digital platforms. It concludes that the central challenge in Europe is not the elimination of this paradox but its governance under conditions of intensified marketisation and platform capitalism. It will be shown, that in future there will be a lot of pressure for public service broadcasters in Europe in the allocation of sports broadcasting rights and in fulfilling their key function. Keywords: public service broadcasting; sports rights; public value, EU media law; competition law; platform capitalism; audiovisual regulation